POMEGRANATE (PUNICA GRANATUM L) AND WOUND HEALING: A REVIEW OF EXPERIMENTAL STUDIES: Pomegranate (Punica granatum L) and Wound Healing - Araujo-Filho, Irami; Batista da Silva, Fabiano; Gonçalves, Giuliana Fulco; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
The review discusses the potential of Punica granatum L., known as Pomegranate, and its extracts in promoting wound healing. This review summarizes current knowledge about the use of Punica granatum L in healing cutaneous wounds in experimental models, mechanisms of action, challenges, and opportunities for future research. Pomegranate extract has been observed to benefit wound healing due to its antioxidant, anti-inflammatory, and antimicrobial properties. The fruit's polyphenols, flavonoids, and tannins contribute to wound healing, reduce oxidative stress, inflammation, and infection, as well as stimulate fibroblast proliferation and collagen synthesis, which are crucial for tissue repair. Animal studies have shown that pomegranate extract accelerated wound closure, re-epithelialization, collagen deposition, and reduced wound size, inflammation, and bacterial load in various wound models. In addition, pomegranate extract in the form of nanoparticles, associated or not with silver, was analyzed for improvement in wound healing, antimicrobial action, and reduction of inflammation in animal models. Pomegranate peel and seed oil enhance collagen synthesis, growth factor expression, and reduce oxidative stress. Pomegranate extract shows promise as a natural and safe alternative for wound healing. The mechanisms underlying Pomegranate's beneficial effects on wound healing were discussed, potential clinical applications of Pomegranate in treating human skin wounds, limitations, and challenges.